Ecophysiological response of Populus alba L. to multiple stress factors during the revitalisation of coal fly ash lagoons at different stages of weathering - Kostić, Olga; Jarić, Snežana; Pavlović, Dragana; Matić, Marija; Radulović, Natalija; Mitrović, Miroslava; Pavlović, Pavle (Frontiers in Plant Science, 2024)
The enormous quantities of fly ash (FA) produced by thermal power plants is a global problem and safe, sustainable approaches to reduce the amount and its toxic effects are still being sought. Vegetation cover comprising long-living species can help reduce FA dump-related environmental health issues. However, the synergistic effect of multiple abiotic factors, like drought, low organic matter content, a deficit of essential nutrients, alkaline pH, and phytotoxicity due to high potentially toxic element (PTE) and soluble salt content, limits the number of species that can grow under such stressful conditions. Thus, we hypothesised that Populus alba L., which spontaneously colonised two FA disposal lagoons at the 'Nikola Tesla A' thermal power plant (Obrenovac, Serbia) 3 years (L3) and 11 years (L11) ago, has high restoration potential thanks to its stress tolerance. We analysed the basic physical and chemical properties of FA at different weathering stages, while the ecophysiological response of P. alba to multiple stresses was determined through biological indicators (the bioconcentration factor (BCF) and translocation factor (TF) for PTEs (As, B, Cr, Cu, Mn, Ni, Se, and Zn)) and by measuring the following parameters: photosynthetic efficiency and chlorophyll concentration, non-enzymatic antioxidant defence (carotenoids, anthocyanins, and phenols), oxidative stress (malondialdehyde (MDA) concentrations), and total antioxidant capacity (IC50) to neutralise DPPH free radical activity. Unlike at L3, toxic As, B, and Zn concentrations in leaves induced oxidative stress in P. alba at L11, shown by the higher MDA levels, lower vitality, and reduced synthesis of chlorophyll, carotenoids, and total antioxidant activity, suggesting its stress tolerance decreases with long-term exposure to adverse abiotic factors. Although P. alba is a fast-growing species with good metal accumulation ability and high stress tolerance, it has poor stabilisation potential for substrates with high As and B concentrations, making it highly unsuitable for revitalising such habitats.